(untitled) (Linguostylistic Studies, 2017)
The article analyzes derivational peculiarities of the socio-political neologisms in the modern Ukrainian language, which have been identified in the publications of the internet-media since 2012. The emphasis is laid on prefixation and suffixation which are the most productive ways of the affixal derivation in this stratum of the lexicon. The importance is placed on the affixes which are actively used in the formation of the Ukrainian neologisms. The revealed examples are examined and described. Despite the quantitative predomination of the new socio-political units formed with the help of prefixes, the suffixation represents more diverse complex. Most of the suffixes are primordially of Ukrainian origin, whereas a lot of prefixes are of international origin. The conducted structural and semantic analysis allowed identifying a new prefix e- and new meaning of the prefix post-, whose development has been influenced by the social and political reality.